👤

b) 1,(6)x[5/2-15/4:4,1(6)]

Răspuns :

[tex]1.(6) \times ( \frac{5}{2} - \frac{15}{4} \div 4.1(6)) = [/tex]

[tex] = 1 \frac{6}{9} \times ( \frac{5}{2} - \frac{15}{4} \div 4 \frac{16 - 1}{90} ) [/tex]

[tex]= \frac{9 + 6}{9} \times ( \frac{5}{2} - \frac{15}{4} \div 4 \frac{15}{90} ) [/tex]

[tex]= \frac{15}{9} \times ( \frac{5}{2} - \frac{15}{4} \div \frac{4 \times 90 + 15}{90} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{5}{2} - \frac{15}{4} \div \frac{375}{90} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{5}{2} - \frac{15}{4} \div \frac{25}{6} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{5}{2} - \frac{15}{4} \times \frac{6}{25} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{5}{2} - \frac{3}{2} \times \frac{3}{5} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{5}{2} - \frac{9}{10} ) [/tex]

[tex]= \frac{5}{3} \times ( \frac{25}{10} - \frac{9}{10} ) [/tex]

[tex]= \frac{5}{3} \times \frac{16}{10} [/tex]

[tex]= \frac{1}{3} \times \frac{8}{1} [/tex]

[tex] = \frac{8}{3} [/tex]